2001
DOI: 10.1002/1529-0131(200103)44:3<541::aid-anr102>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Lymph draining from foot joints in rheumatoid arthritis provides insight into local cytokine and chemokine production and transport to lymph nodes

Abstract: Objective. Rheumatoid arthritis (RA) is characterized by inflammatory reactions in joints and adjacent tissues unaccompanied by clinically evident changes in lymphatics and lymph nodes draining the inflamed areas. The explanation for this phenomenon, which contrasts with infectious processes in joints and soft tissues that evoke major changes in the lymphatic system, is unclear. To determine which inflammatory factors produced in the joints of RA patients are transported in lymph to lymph nodes, we measured le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
2
20
0
1
Order By: Relevance
“…24,44,46 The ratio of TMAbs concentration in tissue and plasma system was 0.057 (0.058 in Ref 23 ). The concentration of endogenous IgG in the interstitial space was 18% of that in plasma, which is consistent with the reported values from the experimental data (≥ 17% in Refs 24,47,48 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…24,44,46 The ratio of TMAbs concentration in tissue and plasma system was 0.057 (0.058 in Ref 23 ). The concentration of endogenous IgG in the interstitial space was 18% of that in plasma, which is consistent with the reported values from the experimental data (≥ 17% in Refs 24,47,48 ).…”
Section: Resultssupporting
confidence: 91%
“…The simulated PK data from published adult/pediatric population PK analysis of two TMAbs were used in this study: bevacizumab for mPBPK model development and palivizumab for external validation of the developed mPBPK model. 10,46 Plasma concentration-time profiles of bevacizumab for adults and pediatric subjects with different weight were simulated using two-compartment linear PK model with the following covariate-parameter relationships for both pediatric and adult subjects; 46 Plasma drug concentrations of both bevacizumab and palivizumab were collected after a single intravenous bolus injection of 10 mg/kg of the antibodies at 1,2,6,8,12,24,48,96,168,336,504,672,840,1008, and 1176 h post injection. In adult subjects, body weights of 50, 60, 70, 80, 90 and 100 kg were used for simulation and fitting.…”
Section: Datamentioning
confidence: 99%
“…Synovial specimens from patients with rheumatoid arthritis (RA) and osteoarthritis have an increased number of lymphatic vessels and increased expression of the lymphatic growth factor vascular endothelial growth factor C (VEGF‐C) (8, 9). Furthermore, clinical reports have described larger lymph nodes (LNs) (10) and increased lymphatic flow rates in lymphatic vessels draining arthritic joints in RA patients (11). Similarly, recent studies of animal models of RA have demonstrated increased lymphatic vessel formation in inflamed joints and in draining popliteal LNs (12–14).…”
mentioning
confidence: 99%
“…It is featured by synovitis with in ltration of in ammatory cells, predominance of catabolic factors including pro-in ammatory cytokines and pro-erosive mediators, and the progressive destruction of cartilage and bone. Clinical study reports that lymph drained from RA joints contains high levels of proin ammatory cytokines and chemokines [1], suggesting that removal of in ammatory factors via the lymphatic vessels (LVs) from synovial space and interstitial tissues may contribute to the pathogenesis of RA. The lymphatic vasculature is composed of capillaries and mature vessels that have different morphologies, structural compositions, and functions.…”
Section: Introductionmentioning
confidence: 99%